Ooid-stromatolite association - a stress for benthic ecosystems - A. I. Antoshkina (Известия высших учебных заведений: Геология и разведка, 2015)
This study reports the occurrence of ooid-stromatolite association (0,5-9 m in thickness) in the Lower Paleozoic sections of the Timan-northern Ural region. Well-preserved different fabrics seen in ancient ooids and stromatolites have previously been interpreted with respect to paleoenvironmental conditions which brought changes in benthic ecosystems. Results from current study suggest that it is possible that the connection of ooids with stromatolites at the time-levels depends on their genetic relationship due to abundance of microbial inhabits during periods of shallow water marine basin regressions. During regression in the result of further paleolandscape differentiation of the bottom the hydrochemical and hydrodynamic regimes of the water reservoir changed. It lead to the quiet-water environments, expansion of microbe and bacterial associations and eutrophy of waters, calcium balance of sea waters fall and reorganization of benthos ecosystems with dominance of mostly euryfacial and euryhaline organisms - Ostracods, gastropods and bivalves. Bulk carbonate values from the Wenlock limestones with ooids average -5,4...-6,4% for S13C PDB and 22,9...24,6% for S18O SNOW. Additionally, a low content of boron 11-30g/t in these limestones also indicates the lowered salinity of waters.